A CDST Perspective on Variability in Foreign Language Learners’ Listening Development - Chang, Pengyun; Zhang, Lawrence Jun (Frontiers in Psychology, 2021)
Within a Complex Dynamic Systems Theory (CDST) framework, this longitudinal qualitative study explored the complex patterns and identified the degree of variability in three learners’ developmental process. Learners’ listening performance was tracked and examined every six weeks, followed by retrospective interviews and self-reflections every seven weeks over the 43-month span. A series of CDST techniques were adopted for data analysis, including using min-max graphs to trace the minimum and maximum scores on the EFL learners’ listening developmental indices over time. Monte-Carlo and Loess smoothing analyses were applied to gauge for degrees of variability. The results suggest that: 1) Min-max graphs and smoothed Loess curves depict flux developmental processes of learners’ L2 listening; 2) learners differed from each other in the degree of inter-individual variability in their listening developmental trajectory; and 3) occurrence of unanticipated patterns confirm that learners demonstrated personalised intra-individual variability within their unique listening developmental process. Results indicate that variability is a pattern characteristic of CDST both between and within individuals, and inform us about how Chinese EFL listeners’ language develops. We conclude by discussing the implications for researchers and practitioners who are concerned with learners’ developmental trajectories and unexpected changing patterns in the process of foreign language learning.